Dawny kościół ewangelicki w Pogorzeli1. Z dziejów przekształceń architektury ewangelickiej w Wielkopolsce - Krzyślak, Bolesława (Ecclesia. Studia z Dziejów Wielkopolski, 2013)
The first dissenters arrived in Pogorzela during the time of the Reformation, but the first prayer house of the evangelical settlers was set up much later. For this purpose they rebuilt a wooden barn from 1778. In this building services were presided over by the parson from the nearby Kobylin, and once a week the teacher from Gumienice preached sermons. In 1853 the first local parson was appointed and so it was possible to establish a separate parish. The construction of the present church lasted from 1860 until October 1861, and on 24 July 1862 it was solemnly consecrated. The church in Pogorzela was built by Friedrich Wilhelm Butzke according to a typical government design by F.A. Stüler. In 1904 the parsonage was built.